Portrait of a Man, Said to be Christopher Columbus (born about 1446... - SebastiaNo del Piombo (Wikimedia Commons, 2026)
Oeuvre issue de Wikimedia Commons pour la demo du fonds documentaire. Titre: Portrait of a Man, Said to be Christopher Columbus (born about 1446....
Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons